IDENTIFICATION OF SPECIFIC AFLP MARKERS FOR SEVEN TILAPIA BREEDS CULTURED IN VIETNAM - Hồng, Trần Thị Bích (Vietnam Journal of Biotechnology, 2011)
Seven Tilapia breeds originated from different countries belonging to two species of Oreochromis aureus and Oreochromis niloticus were used to study the genetic diversity and find out the differences expressing in specific bands. AFLP technique and polyacrylamide 5% for screening were used. DNA of every breed was bulked so that 10 inviduals made 1 sample. Bulked segregant analysis is a rapid mapping strategy suitable for monogenic qualitative traits. When DNA often inviduals are pooled, all alleles must be present. Sixteen primer combinations were tested and bulked samples were established from each population and produced distinctive bands. Moreover, the complexity of DNA fingerprinting varied from one species to another, suggesting that the bulked sample can be particularly useful in breeding programs and hybridization. The results generated from the AFLP analysis were used for drawing the genetic relationships among the examined populations.The presence of band scored 1, the absence was 0. NTSYSpc revealed similarity level between 7 breeds was very high (> 85%), especially among O. aureus or O. niloticus (> 97%). In total 375 bands observed from 16 primer combinations, there were 64 polymorphic bands but only 12 specific bands for 7 breeds such as: AF25/220, AF26/210, AF26/350, AF29/330, AF42/180, AF42/170, AF43/170, AF43/225, AF43/250, AF43/160, AF54125, and AF54180. These specific bands are source of markers development for breeding selection.